Amido modificado de taro (Colocasia esculenta L. Schott): propriedades funcionais - Almeida, Elisândra Costa (2012)
Taro has economic and industrial potential to justify investment in this culture because it is a food with excellent nutritional quality, especially starch, important source of energy, frequently used in the food industry, particularly as gelling and thickening agent, applied in the development of several products. However the starch in its native form has limitations for use, requiring modifications to improve its functional properties and increasing its possibilities for use in the food industry. The objective of this research was to study and compare the properties of native starch extract from taro (Colocasia esculenta L. Schott) clone Macaquinho with its modified starch by oxidation, acid hydrolysis, succinylation, intercross and combination of hydrolysis, succinylation and intercross for use in the food industry. After extraction of the starch, it was modified by oxidation using sodium hypochlorite, hydrolysis with hydrochloric acid, succinylation with succinic anhydride and intercrossing with trimetaphosphate and sodium tripolyphosphate. According to the experiments, it was verified that the native starch extracted from Macaquinho clone contains considerable percentage of starch, low amount of substances contaminants, like proteins or lipids, without influences on the functional properties. After the modifications and combinations occurred in the native starch, they did not showed degree of substitution beyond that permitted by regulatory agencies, being in accordance with Brazilian law. The addition of the substituent groups was decisive in the characterization of the functional properties of taro starch, modified and combined. Microscopy revealed that the starch granules presented circular and polyhedral shapes. The hydrolyzed, succinylated and intercrossed starches suffered major visible alterations in their morphology due to the modifications conducted. The swelling of the granules occurred above 75oC, with prominence for the native, oxidized, succinylated and intercrossed starches, which had their swelling power increased with the increase of temperature. The highest solubility was observed in hydrolyzed starches. The higher water absorption capacity was verified in intercrossed starch and the hydrolyzed starches demonstrated higher oil absorption and paste clarity. The best paste properties were obtained to the oxidized starch, followed by native and succinylated starches, with maximum viscosity at low temperatures. However, the oxidized starch showed higher retrogradation tendency, differently from hydrolyzed starches, more stables. The functional profiles noted in native, modified and combined starches of taro were variables, which provide a lot of possibilities for their use in the food industry.